Cognitive–behavioural therapy with post-session d-cycloserine augmentation for paediatric obsessive–compulsive disorder: pilot randomised controlled trial. (January 2014) - Mataix-Cols, David; Turner, Cynthia; Monzani, Benedetta; Isomura, Kayoko; Murphy, Caroline; Krebs, Georgina; Heyman, Isobel
Summary: A partial N -methyl-d-aspartate agonist, d-cycloserine, enhances fear extinction when given before or shortly after exposure to feared stimuli in animals. In this pilot double-blind placebo-controlled trial (trial number: ISRCTN70977225), 27 youth with obsessive–compulsive disorder were randomised to either 50mg d-cycloserine or placebo administered immediately after each of ten cognitive–behavioural therapy (CBT) sessions, primarily consisting of exposure and ritual prevention. Both groups improved significantly and maintained their gains at 1-year follow-up, with no significant advantage of d-cycloserine over placebo at any time point. The effects of CBT may not be augmented or accelerated when d-cycloserine is administered after sessions.